Corneal Involvement in Wallenberg Syndrome: Case Report and Literature Review. (2nd January 2020) - Pellegrini, Francesco; Interlandi, Emanuela; Cuna, Alessandra; Mandarà, Erika; Lee, Andrew G.
ABSTRACT: A 47-year-old man with Wallenberg syndrome after a stroke in the territory of the left vertebrobasilar artery and posterior inferior cerebellar artery, presented a week later complaining of visual loss in the left eye. Examination showed corneal anaesthesia associated with a neurotrophic corneal epithelial defect. Corneal involvement secondary to trigeminal neuropathy in Wallenberg syndrome is not frequently reported and may lead to epithelial erosion and neurotrophic keratopathy. Clinicians should be aware that visual loss can occur from a neurogenic basis (e.g., Wallenberg syndrome) due to neurotrophic keratopathy. The use of cocaine, a potential cause of neurotrophic keratopathy, should also be suspected in the appropriate clinical scenario.